Analysis of a reversible five-point bending configuration based on a novel two-sense support. (May 2015) - Mujika, F.; Asensio, M.; Vargas, G.; Boyano, A.; De Gracia, J.
Abstract: A novel two-sense support for flexural tests has been designed and manufactured in Ikerlan. The aim of this support is to do two-sense bending fatigue tests. In order to reduce the displacement corresponding to a given stress, a novel test configuration, designated as five-point bending, is modelled analytically. Basically, it is a three-point configuration with two supports at the ends that exert forces in the same sense as the applied load. In this way, a partial clamping is obtained that can be modelled by concentrated loads. The model has been checked carrying out quasi-static three-point and five-point bending tests at different spans in unidirectional carbon/epoxy composite specimens. Flexural modulus and the out-of-plane shear modulus have been obtained by linear regression in both cases, after having obtained experimentally the stiffness of the system.